Medan Translasi Pada Pemetaan Artefak Kebudayaan Berupa Produk Kerajinan - Darmawan, Ruly (PURBAWIDYA, 2025)
This paper aims to present theoretical findings related to the translation field in relation to efforts to reveal the value of the intangibility of cultural artifacts in the form of craft products. The theoretical findings here are ideas obtained when carrying out re-readings that are being carried out (work-in-progress) based on the findings of two previous studies on the manifestation of artifacts that focus on the aspect of human-technology interaction and its interpretation. The re-reading of the two previous research findings is qualitative interpretative in nature that focuses on the translation mode in the process of producing craft products. This re-reading attempts to find the position of the translation field as a complement to awareness when revealing the value of the intangibility of craft products. The findings of this re-reading are expected to be an inspiration for developing a tool that can assist in research activities into craft products and/or cultural artifacts based on the dynamics of cultural translation.